Removal of cadmium from aqueous solution by sorbents produced from plant wastes / Megat Ahmad Kamal Megat Hanafiah, Mohammad Noor Jalil and Suzila Shafie - Megat Hanafiah, Megat Ahmad Kamal; Jalil, Mohammad Noor; Shafie, Suzila (Universiti Teknologi MARA Cawangan Pahang, 2003)
The ability of natural adsorbents (MM, IC and CHF) to remove cadmium from synthetic wastewater was evaluated by comparing with PAC. All experiments were carried out under batch mode. The influence of initial metal concentration has been studied. The order of cadmium removal was found as PAC>CHF>IC>MM. The percentage removal of cadmium at 5ppm by CHF, IC and MM was 88.2, 73.6 and 33.4 respectively. As the metal ion concentration increases, the percentage removal of cadmium decreases. The high percentage removal at low metal ion concentration and low production cost make IC and CHF the attractive sorbents for the removal of cadmium from waste streams.